2019
DOI: 10.5398/tasj.2019.42.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-related Attributes of Raw and Cooked Meat of Culled Saanen Goat Marinated in Ginger and Pineapple Juices

Abstract: The effects of ginger and pineapple juices on pH, color (L*, a*, b*), thiobarbituric acid reactive substances (TBARS), sensory intensity, and sensory preference of culled goat meat were determined. Completely randomized design (CRD) and randomized completely block design (RCBD) were applied for physicochemical attributes and sensory profiles, respectively. In raw condition, the pH of ginger-marinated sample was higher than that of pineapple-marinated sample. The increased trend in pH was found in the ginger-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…The denaturation of myoglobin also affected the color of cooked meat. The less brown color of pineapple juice marinated goat meat after cooking has been reported by Putra et al (2019). This might be associated with the denaturation of myofibril protein by the acids of pineapple juice concomitant with the normal denaturation of globin protein induced by heat during heating.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The denaturation of myoglobin also affected the color of cooked meat. The less brown color of pineapple juice marinated goat meat after cooking has been reported by Putra et al (2019). This might be associated with the denaturation of myofibril protein by the acids of pineapple juice concomitant with the normal denaturation of globin protein induced by heat during heating.…”
Section: Resultsmentioning
confidence: 66%
“…However, the data showed that the hardness and chewiness of cooked goat meat trended to decrease when the sample was marinated in both plant juices for 60 min. Pineapple and ginger contain the proteolytic enzymes, which have been noted in previous studies to have the ability to tenderize tough meat by hydrolyzing tissue fibers (Naveena et al 2004;Putra et al 2019). In the present study, the marinated goat meat with both plant juices had a significantly lower shear force value (P \ 0.05) compared to those of the non-marinated sample.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…(2018) have reported that the addition of ginger powder to feed in the feeding of rabbits limited oxidative changes during the cold storage of raw meat. Putra et al. (2019) showed that marinating goat meat in fresh ginger extract limited oxidative changes during refrigerated storage of both raw and cooked meat.…”
Section: Introductionmentioning
confidence: 99%